2015
DOI: 10.1080/00224545.2015.1071767
|View full text |Cite
|
Sign up to set email alerts
|

Need to Belong, Not Rejection Sensitivity, Moderates Cortisol Response, Self-Reported Stress, and Negative Affect Following Social Exclusion

Abstract: The present study examined if the traits need to belong (NTB) and rejection sensitivity (RS) differentially moderate the impact of experimentally manipulated social exclusion on stress and affect. Participants (N = 132) completed a survey measuring NTB and RS, and then were randomly assigned to be included or excluded during a game of Cyberball. A second survey then assessed perceived stress and negative affect, and a cortisol sample was taken. Controlling for gender and baseline cortisol levels, excluded part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 34 publications
(34 reference statements)
0
44
2
Order By: Relevance
“…On the one hand, individual differences regarding the need to belong or self-esteem seem to be important for emotional, hormonal and neural responses (Beekman et al 2015;Ford and Collins 2010;Onoda et al 2009). On the other hand, there are external factors which seem to influence the perception of exclusion in the Cyberball task.…”
Section: Introductionmentioning
confidence: 98%
“…On the one hand, individual differences regarding the need to belong or self-esteem seem to be important for emotional, hormonal and neural responses (Beekman et al 2015;Ford and Collins 2010;Onoda et al 2009). On the other hand, there are external factors which seem to influence the perception of exclusion in the Cyberball task.…”
Section: Introductionmentioning
confidence: 98%
“…During this CBG, participants play a computer-simulated ball and feel distressed during the period when the other players barely throw a ball to him/her. Some studies also showed physiological changes such as raised cortisol level, higher skin conductance, and increased facial temperature [29][30][31][32][33][34]. A systematic review of neuroimaging studies summarized the relevant brain activities and showed its reliability to induce social stress in healthy volunteers [35].…”
Section: Introductionmentioning
confidence: 99%
“…Another issue that was not considered in the current paper was the question of whether participants believed to interact with an avatar (i.e., a human-controlled character) or an agent (i.e., a computer algorithm). The Threshold Model of Social Influence (Blascovich et al, 2002) assumes that the degree of agency attributed to the virtual other influences the interaction. Other authors, however, have succeeded in demonstrating that it does not matter whether the Cyberball-players are controlled by a human or a computer (e.g., Kothgassner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%